2008
DOI: 10.1007/s10456-008-9100-x
|View full text |Cite
|
Sign up to set email alerts
|

Slits and Roundabouts in cancer, tumour angiogenesis and endothelial cell migration

Abstract: Angiogenesis describes the development of new blood vessels from pre-existing vessels. The hijacking of this physiological process by tumours allows them to develop their own supplies of nutrients and oxygen, enabling their growth and metastasis. A large body of literature has accumulated over the last 20 years relating to angiogenesis, including signalling pathways involved in this process. One such pathway uses Slit-Roundabout proteins that are implicated in the development of cancers and tumour angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
129
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 55 publications
2
129
0
Order By: Relevance
“…15,16 Although COL6A3 has not been associated with tumorigenesis, alterations of extracellular matrix-binding proteins would seem necessary for progression and invasion of the dermis by squamous cell carcinoma. The downregulated genes CASZ1, RTN4 (Nogo-A), and NFIB also have been associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although COL6A3 has not been associated with tumorigenesis, alterations of extracellular matrix-binding proteins would seem necessary for progression and invasion of the dermis by squamous cell carcinoma. The downregulated genes CASZ1, RTN4 (Nogo-A), and NFIB also have been associated with tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ROBO3 and ROBO4 are receptors of SLIT and are involved in neuronal axis formation, angiogenesis, etc. 20, 21 Narayan et al 22 reported methylation (36%) of ROBO3 in CACX with no detectable expression of ROBO3 in normal cervix and CACX cell lines. However, the deletion status of ROBO3 and ROBO4 in tumor is not known.…”
mentioning
confidence: 99%
“…20 Although it was recognized as pivotal regulator in the development of central nervous system, 21 slit/ROBO1 signal was also reported to play a role in modulating chemotaxis of T cells and tumor angiogenesis. 22,23 More evidence showed that the secreted slit2 protein mediated chemorepulsive signal on ROBO1 expressing cells, and a chemorepulsive mechanism induced by the interaction between slit2 and ROBO1 might drive glioma and breast cancer cells migration.…”
Section: Discussionmentioning
confidence: 99%